Association between alcohol flushing syndrome and cancer: a systematic review and meta-analysis - Sim, Wilson (2024)
Introduction: Alcohol flushing syndrome (AFS) is experienced by up to 46% of East Asians. This study aimed to review the risk of cancers in AFS patients, elucidate an exposure-response relationship, and understand risk associated with alcohol intake and cancer. Method: An electronic database search of PubMed, Embase, Scopus and Cochrane Library was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. Observational studies on AFS’ effects and all cancers risk were included. Studies including patients with existing malignancy were excluded. Dichotomous variables were pooled using the Mantel-Haenszel method with a random effects model. Sensitivity and subgroup analyses were performed. PROSPERO (CRD42023392916) protocol was followed. Results: A total of 18 articles were included in the final analysis with a total of 387,521 participants. AFS was associated with an increased risk of all cancers (odds ratio [OR] 1.19, 95% confidence interval [CI] 1.06–1.34), esophageal squamous cell carcinoma (OR 1.47, 95% CI 1.05–2.05) and gastric adenocarcinoma (OR 1.40, 95% CI 1.14–1.72). Men with AFS exhibited an increased risk of all cancers (OR 1.34, 95% CI 1.13–1.59). However, this was not observed in women. All cancers risk was associated with AFS in those who consumed drink (i.e. consumed alcohol) more than 200 g of pure ethanol/week (OR 1.68, 95% CI 1.20–2.37) but not those who consumed less than 200 g of pure ethanol/week (OR 1.27, 95% CI 0.90–1.79) or non-drinkers (OR 0.99, 95% CI 0.67–1.47). Conclusion: AFS is associated with an increased risk of all cancers, particularly esophageal squamous cell carcinoma and gastric adenocarcinoma.